Religious Moderation in the Qur'an and Hadith: Theological Foundations and Implications for Contemporary Life - Yansah, Savri; Zubaedi; Toha Andiko; Moch. Iqbal (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Religious moderation is an important principle in Islamic teachings which is reflected in the teachings of the Qur'an and hadith. Islam was revealed as a religion that brings grace, balance, and justice to the entire world. This article aims to examine the foundations of religious moderation from the perspective of the Qur'an and hadith and its relevance in the context of multicultural and multireligious society. With a thematic approach and normative analysis, this article highlights the importance of tawassuth (middle), tasamuh (tolerance), and i'tidal (fair) attitudes in strengthening social cohesion and maintaining world peace. This research seeks to reveal religious moderation in the Qur'an and the hadith "Theological Foundations and Its Implications for Contemporary Life". The research method in this article is qualitative research with a literature study. Literature research is through literature-based literature research, which is the main source in the form of library data in the form of books, manuscripts, books, and other sources in the form of other documentation related to religious moderation. The results of the study show that religious moderation refers to a fairly important and controversial issue that has been discussed during this decade. Minister of Faith Lukman Hakim Saifuddin is very enthusiastic about facing this problem because he believes that by applying the concept of religious moderation, uproar in society can be overcome, especially the problem of feuds between religious people and between religious people themselves. Radicalism, religious violence and terrorism have always been associated with Islamic gangs, despite the fact that they are a real group. The Quran, which is the holy book, and the Hadith, which is the words of the Prophet Muhammad, give Muslims a guide to life and guidance for everything they face in their daily lives.  The Quran and Hadith have offered religious moderation centuries ago. This means being religious by taking a middle way, maintaining balance, avoiding excess, and not being extreme. Not even within the bounds of religious moderation when dealing with plural citizens, but more broadly and universally. One of the main characteristics of Islamic teachings, which derives from the Qur'an and hadith, is religious moderation. Moderation values such as tawassuth, tasamuh, and i'tidal must be maintained in religious practice and social life to meet the challenges of the complex and diverse modern world. Muslims have the ability to contribute to peace, justice, and humanity both at the local and international levels with moderation.